Pengaruh Senam Nifas Terhadap Involusi Uteri Pada Pasca Persalinan Normal di Puskesmas Semambawa Nias Selatan Tahun 2023 - Bertin Zebua; Adelina Sembiring; Lisbet Gurning (Pusat Riset dan Inovasi Nasional, 2024)
Postpartum exercise is exercise that is carried out from the first day of birth every day until the tenth day, consisting of a series of body movements carried out to speed up the mother's recovery. The aim of postpartum exercise is to help speed up the mother's recovery, speed up the involution process and restore the function of the womb. The benefits of postpartum exercise include improving blood circulation, body and back posture after giving birth, improving muscle tone, pelvic and abdominal muscle stretching and helping mothers to be more relaxed and fresh after giving birth. Postpartum exercise is rarely done because postpartum mothers are afraid to do a lot of movement, are afraid of the stitches coming out, the perineal wound still hurts and there is a belief that has developed and is believed by society, namely that if it has not been 40 days after giving birth, the mother is not allowed to do activities. The aim of the research was to determine the effect of postpartum exercise on uterine involution during normal postpartum delivery at the Semambawa Community Health Center BPM, South Nias in 2023.This research used a quasi-experimental research design with a post test only design with one comparison treatment, the sample in the research was 30 people using a Random Sampling System. The data collected in the research is primary data, namely data obtained directly from respondents. The data analysis used was the Wilcoxon signed ranks test.The results of research on uterine involution before postpartum exercise intervention during normal postpartum delivery, the majority experienced subinvolution, 30 people (100%), uterine involution after postpartum exercise intervention during normal postpartum period, the majority experienced normal, 22 people (73.3%), there was an effect Postpartum exercise on uterine involution in normal postpartum with a value of p=0.000 p<0.05. So Ho is rejected and Ha is accepted, which means that there is an influence of postpartum exercise on uterine involution during normal postpartum delivery at the Semambawa Community Health Center, South Nias in 2023. Midwives are expected to improve and provide midwifery services by applying postpartum exercise methods and relaxation techniques to postpartum mothers so that the process of uterine involution goes well.